Learning DCOM - Thai, Thuan L. (O'Reilly, 1999)
"This book introduces C++ programmers to DCOM and gives them the basic tools they need to write secure, maintainable programs. While using Visual C++ development tools and wizards where appropriate, the author never leaves the results up to magic. The C++ code used to create distributed components and the communications exchanged between systems and objects are described at a level where the reader understands their significance and can use the insights for such tasks as debugging and improving performance." "This book is for anyone who wants to understand DCOM. While thoroughly practical in its goals, it doesn't stint on the background you need to make your programs safe, efficient, and easy to maintain."--Jacket.